Гельдеровость функций из класса Bq,s - Скрыпник, И.В. (Український математичний журнал, 1993)
A class of functions Bq,s is defined which contains generalized solutions to some higher order quasilinear parabolic equations. We prove that Bq,s is imbedded in the space of Holder functions.